Socio-Cultural And Economic Drivers of Forced Motherhood and The Coping Mechanisms of Domestic Violence Survivors - Omojemite, Matthew Damilola (Journal of Cultural Analysis and Social Change, 2026)
The purpose of this study was to determine the socio-cultural and economic factors contributing to forced motherhood among women experiencing domestic violence in Ekiti State, Nigeria, and to identify coping strategies adopted by affected women and children. The study employed a descriptive survey research design within the quantitative paradigm. The population comprised women aged 18–49 who had experienced domestic violence, alongside key informants such as social workers, healthcare providers, and child psychologists. A purposive multistage sampling technique was used to select 200 respondents from three urban and semi-urban Local Government Areas with gender-based violence response centers. Data were collected using a researcher-developed Domestic Violence and Forced Motherhood Questionnaire (DVFMQ), structured on a 4-point Likert scale. Validity was ensured through expert reviews in gender studies, psychology, and public health, while reliability was confirmed via a pilot test, which yielded a Cronbach’s alpha of 0.80. The instrument was administered both orally and in writing, using English or Yoruba to accommodate respondents’ literacy levels. Descriptive statistics and binary logistic regression analysis were applied at a 0.05 significance level to analyze the data. Findings revealed that socio-cultural factors like stigma of divorce, community silence on domestic violence, and reproductive expectations strongly influence forced motherhood. Economic factors, especially financial dependence, poverty, and unemployment, significantly predict forced motherhood in both urban and rural areas. Coping strategies mainly involved emotional and spiritual support, with formal reporting to authorities being low. Based on these findings, the study recommends economic empowerment programs, culturally sensitive community education, strengthened formal and informal support systems, and legal reforms to improve women’s reproductive autonomy and safety.